2019
DOI: 10.1177/2158244018825027
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Proximity and Genre Proximity: How Do Chinese Viewers Enjoy American and Korean TV Dramas?

Abstract: In China, watching foreign television dramas is not only an important means to know about the outside world but also a trendy lifestyle. With the images of modern lives and exotic flavors, foreign TV dramas satisfy the increasing tastes of petit bourgeois in China, who yearn for prosperity, comfort, fashion, and hedonism (Chan & Ma, 1996; Jiang & Leung, 2012; Xu, 2007). The popularity of foreign TV dramas reflects the cultural logic of media globalization, which is shaped in two competing processes-globalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
12
0
1
Order By: Relevance
“…Such relativity reflects the media consumer's taste and preferences for cultural goods (Bourdieu, 1984). As two types of representative transnational media consumption, American dramas and Korean dramas provide different narratives and attract different audiences in China (Lu et al, 2019). This study found that gender, age, education background, and income exhibit different roles in predicting the transnational media consumption dissonance generated from American and Korean dramas in line with previous research (Jiang and Leung, 2012).…”
Section: Concluding Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Such relativity reflects the media consumer's taste and preferences for cultural goods (Bourdieu, 1984). As two types of representative transnational media consumption, American dramas and Korean dramas provide different narratives and attract different audiences in China (Lu et al, 2019). This study found that gender, age, education background, and income exhibit different roles in predicting the transnational media consumption dissonance generated from American and Korean dramas in line with previous research (Jiang and Leung, 2012).…”
Section: Concluding Discussionsupporting
confidence: 83%
“…As American dramas displayed more women's independence, when individuals' watch more American dramas than Chinese dramas, agreement on GRIM would be further weakened by the reduction of benevolence sexism values. However, because of cultural proximity, the genderrelations depicted in Korean and Chinese dramas may share more similarity (compared with American dramas) (Lu et al, 2019). Hence, when individuals consume more Korean dramas than Chinese domestic dramas, the hostile and benevolence sexism values are strengthened, thereby fortifying their agreement on GRIM.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study conducted by Ida (2008) shows that the concept of 'cultural proximity' has a role in driving the popularity of Korean drama in Indonesia. However, Lu, Liu and Cheng (2019) finds that cultural proximity could not explain the enjoyment of Chinese audiences consuming Korean TV Dramas. Ng and Chang (2019) confirms that Hong Kong audiences do not get a high impact from Korean TV dramas.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Also, Kang et al (2014) found that, despite the popularity of K-drama, the majority of viewers of K-drama were those with lower income and education level or those with a higher education level but lower income, whilst a majority of viewers with a higher income still preferred American dramas. Lu et al (2019), in their study on Chinese viewers, found that cultural proximity explained involvement with K-drama while genre proximity and enjoyment belonged to American dramas.…”
Section: Hallyu 10 As a Transnational Popular Culturementioning
confidence: 98%